(untitled) (Research, Society and Development, 2020)
Enteropathogens such as Salmonella spp. and Escherichia coli are important health challenges in the poultry production chain, because when installed in the production chain, they impair the safety of food supply. The determination of the microbiological quality of chicken meat, especially when marketed in spiced form, is necessary, given that consumer prefer this type of processed protein. This work aims to evaluate the microbiological quality of the meat of seasoned chicken marketed in the municipality of Rio Verde, Goias, using Salmonella spp. and Escherichia coli as target microorganisms, and considering as variables the type of establishment, validity date and presence of municipal inspection seal. From 80 analyzed samples, 30% (24/80) of samples were positive for Salmonella spp. and 55% (44/80) for E. coli. Regarding the type of establishment, it was observed that 27.45% (14/51) of supermarket samples and 34.48% (10/29) of meat store samples were contaminated by Salmonella spp. Considering E. coli, 49.01% (25/51) of supermarket samples and 65.55% (19/29) of meat store samples were positive for this pathogen. 80% (64/80) of the samples had the municipal inspection seal (MIS), and 83.75% (67/80) contained the expiration date on the label. The legislation in its narrative guarantee’s protection for the consumer with regard to the presence of pathogenic serotypes of these agents, however, it is worth noting that the effective action of health surveillance, and the constant laboratory investigation of the products are necessary.